(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
“The memoirs that Don Félix María Calleja, sixtieth Viceroy of New Spain and frustrated liberator of Mexico, never wrote” is the subtitle that accompanies this novel by José Manuel Villalpando, through which its author explains one of the resources of the new novel. Historical, what is the attribution of a non-existent manuscript to a leading figure of the Independence of Mexico (Review)